The algorithm of investigation of deformations of solids with contact interaction - Abdrakhmanova, A I; Sultanov, L U (Journal of physics. Conference series, 2019)
The work is devoted to the construction of a computational algorithm for investigation of finite deformations of solids with contact interaction. Contact interaction of solids is an actual issue due to it is one of the most common methods of transferring external forces in practice and encounter in many engineering tasks. A master-slave algorithm is used to build a contact interaction model. To perform the contact conditions in finite element implementation of the penalty method is used. The contact problem is formulated in a variational formulation. A resolving equation in the actual state is obtained, which, with the help of linearization and the finite element method, reduces to a system of linear algebraic equations.